(untitled) (Journal of Partial Differential Equations, 2001)
This paper is devoted to the Cabn-Hilliard equation with degenerate mobility in two spatial variables with a typical case modelling thin viscous film spreading over a solid surface. We establish tbe existence of radial symmetric solutions with the property of finite speed of perturbations.